Modelos de comportamiento y modelos teóricos - Alberto M. Cirese (Estudios sobre las Culturas Contemporáneas)
In this article the author outlines the theoretical and methodological differences that exist in the ways of conceptualizing logico-mathematical and empirical science. In describing types of models of behavior as theoretical constructions, the author establishes that in the ethno-anthropological field the concept of a model assumes at least two values: the realization of a formal model, that governs action or the representation of whatever universe of enq)irical facts that is an intrtiment or product of investigation and knowledge of reality.